1984
DOI: 10.1161/01.res.54.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-adrenergic-mediated reduction in coronary blood flow secondary to carotid chemoreceptor reflex activation in conscious dogs.

Abstract: SUMMARY. We examined the late coronary vascular response to carotid chemoreceptor reflex activation in normal, conscious dogs instrumented for the measurement of right main and left circumflex coronary artery blood flows, arterial and right ventricular pressures, and arterial and coronary sinus blood gases and O 2 contents. With heart rate held constant by electrical stimulation, and with respiration controlled or allowed to vary spontaneously, carotid chemoreceptor reflex activation (induced by intracarotid n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…The coronary vasodilatation seen in the present study is similar to that which has PULMONARY CHEMOREFLEX AND CORONAR Y RESISTANCE 287 been observed previously during carotid sinus nerve stimulation (Hackett, Abboud, Mark, Schmid & Heistad, 1972), peripheral chemoreceptor stimulation (Hashimoto, Igarashi, Uei & Kumakura, 1964;Vatner & McRitchie, 1975;Vatner, 1983;Murray, Lavallee & Vatner, 1984), carotid sinus baroreceptor stimulation (Ito & Feigl, 1985), and the Bezold-Jarish reflex (Feigl, 1975). Further, the neurohumoral basis for the changes in coronary resistance evoked by capsaicin in the present study is comparable to that seen in previous studies.…”
Section: G a Ord Wa Y And K H Pitettisupporting
confidence: 91%
“…The coronary vasodilatation seen in the present study is similar to that which has PULMONARY CHEMOREFLEX AND CORONAR Y RESISTANCE 287 been observed previously during carotid sinus nerve stimulation (Hackett, Abboud, Mark, Schmid & Heistad, 1972), peripheral chemoreceptor stimulation (Hashimoto, Igarashi, Uei & Kumakura, 1964;Vatner & McRitchie, 1975;Vatner, 1983;Murray, Lavallee & Vatner, 1984), carotid sinus baroreceptor stimulation (Ito & Feigl, 1985), and the Bezold-Jarish reflex (Feigl, 1975). Further, the neurohumoral basis for the changes in coronary resistance evoked by capsaicin in the present study is comparable to that seen in previous studies.…”
Section: G a Ord Wa Y And K H Pitettisupporting
confidence: 91%
“…Although a carotid body chemoreceptor reflex influence on coronary vessels has been demonstrated (Hackett et al, 1972;Vatner and McRitchie, 1975;Murray and Vatner, 1983;Murray et al, 1984), these receptors have been shown to be relatively insensitive to arterial pressure in the range of 60-220 mm Hg (Biscoe et al, 1970;Mancia, 1975). Thus, the reflex observed in the present study most likely originated from carotid sinus baroreceptors.…”
Section: Neural Controlmentioning
confidence: 48%
“…These neural pathways can be reflexly activated by several stimuli. Parasympathetic coronary vasodilation is part of the BezoldJarisch reflex (Feigl, 1975) and the carotid body chemoreflex (Hackett et al, 1972;Vatner and McRitchie, 1975;Murray and Vatner, 1983;Murray et al, 1984). Reflex sympathetic a-receptor coronary 493 vasoconstriction in response to carotid sinus hypotension has been reported in preparations with fireceptor blockade (Feigl, 1968;DiSalvo et al, 1971;Powell and Feigl, 1979) and without /3-receptor blockade (Mohrman and Feigl, 1978).…”
Section: Neural Controlmentioning
confidence: 99%
“…84 With controlled ventilation, a significant a-adrenoceptormediated coronary constrictor response is apparent in conscious dogs during carotid chemoreceptor activation. 85 Several central nervous sites from which aadrenergic coronary constriction can be elicited have been identified in anesthetized cats.86 However, a physiological or pathological role for these central nervous sites in regulating coronary blood flow remains to be established. a-Adrenergic coronary constriction during exercise.…”
mentioning
confidence: 99%